PENGARUH PENGGUNAAN TIPE WORD SQUARE TERHADAP HASIL BELAJAR PKN KELAS III SDN 05 PONTIANAK - Aulia, Syarifah Aisyah; Salimi, Asmayani; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyse the influence by using type word square against the learning outcome of citizenship education the thrid of elementary school 05 pontianak kota. This Study used a quasi-experimental experiment method, with an experimental design of Non-Equivalent Control Group Design. The population in this study is all third grade Elementary School 05 Pontianak Kota. Subjects in this study are whole students of the third class of A which are 25students as an experimental class and third class of B which are 26 students as a control group/class. Data collection techniques used are measurement techniques, with data collection tools in the form of 35 objective tests. Then the analysis is done using the t-test. Based on the results of the analysis obtained t-count (3,515) > t-table (1,678) then Ha is accepted. So it can be concluded that there are differences in civics lesson scores between students who used the type Word Square and students who did not use the type Word Square. From the calculation of the effect size obtained ES of 0,69 (medium criteria). It means learning the influence by using type Word Square against the learning outcome of citizenship the thrid grade of elementary school 05 Pontianak Kota.    Keyword:The Influence, Theory Of Type Word Square, Civics Lesson Scores.